Effects of Terminal Sterilization on PEG‐Based Bioresorbable Polymers Used in Biomedical Applications. Issue 10 (October 2016) - Bhatnagar, Divya; Dube, Koustubh; Damodaran, Vinod B.; Subramanian, Ganesan; Aston, Kenneth; Halperin, Frederick; Mao, Meiyu; Pricer, Kurt; Murthy, N. Sanjeeva; Kohn, Joachim
Abstract : Biomaterials used for medical device applications need to be terminally sterilized before implantation. Some of the sterilization methods can adversely affect the physicochemical properties of device components, such as polymers. The Effect of different sterilizations on the structural, thermal, and morphological properties of moisture‐sensitive bioresorbable poly(ethylene glycol)‐based polymers illustrates the critical role of chemical composition and suggests optimized sterilization conditions. Abstract : The effects of ethylene oxide (EO), vaporized hydrogen peroxide (VHP), gamma (γ) radiation, and electron‐beam (E‐beam) on the physiochemical and morphological properties of medical device polymers are investigated. Polymers with ether, carbonate, carboxylic acid, amide and ester functionalities are selected from a family of poly(ethylene glycol) (PEG) containing tyrosine‐derived polycarbonates (TyrPCs) to include slow, medium, fast, and ultra‐fast degrading polymers. Poly(lactic acid) (PLA) is used for comparison. Molecular weight ( M w ) of all tested polymers decreases upon gamma and E‐beam, and this effect becomes more pronounced at higher PEG content. Gamma sterilization increases the glass transition temperature of polymers with high PEG content. EO esterifies the carboxylic acid groups in desaminotyrosol‐tyrosine (DT) and causes significant degradation. VHP causes hydroxylation of the phenyl ring, and hydrolytic degradation. This study signifies the importance of the chemical composition when selecting a sterilization method, and provides suggested conditions for each of the sterilization methods.